2001
DOI: 10.1002/chin.200106141
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of New Furan‐Derived N‐Substituted Aminomethanephosphonates.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…However, it was proven in papers [2][3][4][5][6][7][8][9][10] that the addition of dialkyl or diaryl phosphites to N-alkyl terephthalic Schiff bases led to the exclusive formation of one diastereoisomeric form. Our previous study [6][7][8][9] revealed that this diastereoisomer was the meso form. On the other hand, the addition of dialkyl or diaryl phosphites to N-aryl terephthalic Schiff bases led exclusively either to the formation of the meso form or to both diastereomeric forms, which depended on the nature of the aryl substituent [8,9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was proven in papers [2][3][4][5][6][7][8][9][10] that the addition of dialkyl or diaryl phosphites to N-alkyl terephthalic Schiff bases led to the exclusive formation of one diastereoisomeric form. Our previous study [6][7][8][9] revealed that this diastereoisomer was the meso form. On the other hand, the addition of dialkyl or diaryl phosphites to N-aryl terephthalic Schiff bases led exclusively either to the formation of the meso form or to both diastereomeric forms, which depended on the nature of the aryl substituent [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Later papers authored by Finocchiaro et al [2][3][4] and Gancarz et al [5] presented the discussion on the stereochemical aspect of these reactions. Our group has also contributed to this topic reporting about the stereochemistry of addition reactions to various N-substituted terephthalic imines [6][7][8][9]. A comprehensive and detailed report on NMR spectroscopic and molecular modeling studies of 1,4-phenylene-bis-aminomethane-bisphosphonates and related structures is given in [10].…”
Section: Introductionmentioning
confidence: 99%
“…Using this methodology, we recently obtained some phenylene-bisaminomethanephosphonates, and an unusual stereochemical outcome of these reactions was pointed out. It was demonstrated that such bisaddition to phenylene-bisimines is highly stereoselective though some exceptions were also noted [4]. In order to explain the mechanism of these reactions, we restudied our previous investigations on a single addition of phosphites to chiral Schiff bases [5][6][7], considering this as a model process.…”
mentioning
confidence: 99%